PWE-146 Pain endophenotypes display complex subcortical brain morphological differences influenced by autonomic neurophysiology or personality traits. (8th June 2018) - Ruffle, Dr James; Coen, Steve; Giampietro, Vincent; Williams, Steven; Aziz, Qasim; Farmer, Adam
Abstract : Introduction: Visceral pain is influenced by an array of individual factors. We have previously coalesced many of these, reporting that two major endophenotypic 'pain clusters' exist: Pain Cluster 1 (PC1), in comparison to Pain Cluster 2 (PC2), had higher neuroticism and anxiety scores, higher baseline sympathetic tone and serum cortisol, but during acute pain had a lower stimulus tolerance and increased parasympathetic tone. Meanwhile, PC2 had the converse profile at baseline and during pain. Endophenotypes were reproducible if reassessed annually, and the two most influential factors in allocating PCs were personality trait neuroticism and autonomic tone. We therefore hypothesised that PCs could linked to altered subcortical morphology. Methods: Endophenotype were determined in 27 healthy subjects (14 male; mean age 30 years, PC1 (n≥11) and PC2 (n≥16), and all underwent structural neuroimaging. Subcortical morphological changes were studied contingent on PC. By alternate regression of PC factors, autonomics and personality traits, we analysed if PC associated brain morphology was affected by autonomic or personality-driven effects. Results: Neuroticism-driven effect PC1 subjects exhibited morphological deformation differences localised to the right amygdala and pallidum, when contrasted to PC2 subjects with effect of autonomic tone regressed. Autonomic-driven effect: Sympathetic tone (cardiac sympathetic index), with regression of personality trait neuroticism, was positively linearly associated with structural deformation changes at the left pallidum, right nucleus accumbens and right putamen (figure 1). Conclusions: Personality and autonomic neurophysiology influences subcortical morphological changes identified in PCs. Future research should investigate associations of endophenotypic characteristics to brain structure and function in health and chronic visceral pain to establish biomarkers for personalised medicine-based approaches.